Reproductive Traits of the Vent Crab Segonzacia mesatlantica (Guinot, 1989) From the Mid-Atlantic Ridge - Cruz, Mariana; Le Bris, Nadine; Colaço, Ana (Frontiers in Marine Science, 2022)
Characteristics on the life-history biology of hydrothermal vent species are a prerequisite to understand the dispersal, population connectivity and ecology of these insular populations. The vent crab Segonzacia mesatlantica (Guinot, 1989; Brachyuran: Bythograeidae) is one of the most dominant endemic predators at deep-sea hydrothermal vents along the Mid-Atlantic Ridge (MAR). However, the biological life-history characteristics remain poorly understood for this species. The objective of this study was to reveal relevant characteristics on the life- history biology of S. mesatlantica, contributing to a better understanding on its reproductive ecology and the importance for the maintenance of healthy populations. The reproductive ecology of S. mesatlantica from the Broken Spur vent field such as the in situ behaviour of brooding females, gametogenesis, fecundity and the embryonic and larvae development was studied. In contrast to non-brooding crabs, brooding females of S. mesatlantica were observed at the vent periphery exhibiting a sequence of specific brooding behaviours, suggesting that they might be providing oxygen to their embryo mass. Results from histological analysis reveal the presence of oocytes in different stages of development within the gonad. Once extruded, the mature oocytes form an egg mass underneath the abdomen that undergoes through embryonic development. Similar to other bythograeid crabs, the egg mass of S. mesatlantica was composed by a high number of relatively small eggs in different stages of embryonic development. The eggs hatch as a first zoea that undergoes through at least four stages of development.